2016
DOI: 10.1002/syn.21945
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lamotrigine on epilepsy‐induced cognitive impairment and hippocampal neuronal apoptosis in pentylenetetrazole‐kindled animal model

Abstract: Purpose: Lamotrigine (LTG) is a broad-spectrum antiepileptic drug that is widely used in clinic. However, the effect of LTG on cognition and neurodegeneration during epilepsy treatment remains controversial. In this study, we compared the cognitive effects of LTG and sodium valproate in pentylenetetrazole (PTZ)-kindled animal model, and the dose dependency was tested for LTG.Methods: PTZ-kindled animals were divided into the following treatment groups: control group, treated with 3.5 mL/kg of 0.9% sodium chlor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…Neural cell death after epilepsy includes necrosis and apoptosis [18]. A previous study shows that number of apoptotic cells has increased at 1 day after seizure and is significantly larger than that in the control group until the seventh week, suggesting that apoptosis runs through the course of epilepsy in rats [19]. Another study shows that neuronal apoptosis partially participates in the formation of hippocampal sclerosis in epileptic patients [19].…”
Section: Discussionmentioning
confidence: 99%
“…Neural cell death after epilepsy includes necrosis and apoptosis [18]. A previous study shows that number of apoptotic cells has increased at 1 day after seizure and is significantly larger than that in the control group until the seventh week, suggesting that apoptosis runs through the course of epilepsy in rats [19]. Another study shows that neuronal apoptosis partially participates in the formation of hippocampal sclerosis in epileptic patients [19].…”
Section: Discussionmentioning
confidence: 99%
“…Epilepsy is mainly characterized by the occurrence of spontaneous recurrent seizures (SRS) and high prevalence of comorbidities, such as cognitive impairments, depression, and anxiety, affecting the lives of individuals (Keezer et al., 2016). Chronic epilepsy is characterized by repeated unpredictable seizures, impairing memory in 30–40% of patients under long-term anti-epileptic drugs (AEDs) treatment, so epilepsy and AEDs both are responsible for memory problems (Helmstaedter, 2002; Canevini et al., 2010; Zhang et al., 2017). Despite there being more than 20 mainstream AEDs, they only provide symptomatic treatment rather than interfering with the disease’s mechanism, and 30% of patients do not respond to current AEDs (Remy and Beck, 2005; Chen et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Pentetrazol, as a central stimulant, can cause neuronal apoptosis in the central nervous system (CNS), especially in the hippocampus area. 5,6 Aer intraperitoneal injection of pentetrazol, rats show a series of behavioral abnormalities and neurological decits. Researches have shown that the concentrations of hydrogen peroxide and nitric oxide are increased while the activities of antioxidant enzymes are decreased following pentetrazol administration in the cultured neurocytes and in a pentetrazol-exposed rat model.…”
Section: Introductionmentioning
confidence: 99%